Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja dan Kedisiplinan Guru - Fitrotul Uyun; Aan Fadia Annur (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to determine the leadership strategies of school principals in improving the performance and discipline of teachers at Madrasah Ibtidaiyah Salafiyah Syafiiyah Hadirul Ulum Tasikrejo Pemalang, Central Java, as well as to identify the supporting and inhibiting factors when these leadership strategies are implemented. This study uses field research with a descriptive approach. The data collected was verbal data or words rather than numbers. The location of this research was at MI Salafiyah Syafi'iyah Hadirul Ulum Tasikrejo, Pemalang Regency. The informants in this study were the principal and classroom teachers. The data collection techniques used were observation, interviews, and documentation. The results of the study found by the researcher regarding the principal's strategy in improving teacher performance and discipline at MI Salafiyah Syafi'iyah Hadirul Ulum Tasikrejo, Pemalang Regency, are as follows: (a) conducting supervision (b) setting an example (c) motivating teaching staff (d) providing adequate facilities and infrastructure (e) providing opportunities to attend training or education (f) conducting evaluations. Meanwhile, the supporting and inhibiting factors are divided into several parts. First, there are two supporting factors, namely (a) a sense of togetherness and kinship within the school environment, and (b) the principal's commitment to improving school quality. Meanwhile, there are two inhibiting factors, namely (a) the suboptimal time management of teachers and (b) the work environment. Based on the results of this study, it can be concluded that the principal's leadership strategy plays a very important role in improving the performance and discipline of teachers at MI Salafiyah Syafi'iyah Hadirul Ulum Tasikrejo, Pemalang Regency. The implementation of appropriate strategies, supported by a sense of togetherness and the principal's commitment, can have a positive impact on teacher professionalism. However, there are still several inhibiting factors that need attention so that the implementation of leadership strategies can run more optimally.